(untitled) (Patan Pragya, 2021)
Economic sectors are broadly categorized as formal and informal sectors. Informal sector is also known as informal economy and grey economy. Informal sectors are beyond the monitoring system and tax system of government. To explore social and economic effects ofcovid-19 on informal sector’s women, this study is conducted as the title of effects of covid-19 pandemic on informal sector’s women in damak, Jhapa. It is based on the theoretical assumption of feminism. It employs exploratory research design and is based on both primary and secondary sources of data. The study revealed that there are very bad effects ofcovid-19 pandemic on women’s livelihood, who are involved in informal economic sectors especially in street vending. The pandemic has indeed affected by decreasing the income of the women. The working condition in regards to hours of work per day and days of work per week has decreased significantly affecting the income. Additional problems such as less customer flow, low income, increased municipality eviction and lack of supplies of goods increased and led to indebtedness, and no saving at all during the pandemic. It suggests that concerned authorities should make effective institutional frameworks to empower women involved in informal sector of economy.